Phytophthora Identification and Sampling in Citrus Nurseries - Jamie D. Burrow; Diane B. Bright; Tim D. Riley; James H. Graham (EDIS, 2015)
Phytophthora species are important soil-borne, fungus-like pathogens that attack the root systems, trunk, and fruit of citrus trees at any age. The front of this identification sheet includes images of healthy and infested roots and descriptions of leaf and root symptoms. The back lists sampling procedures: soil collection, soil testing, and diagnosing phytophthora. Written by Jamie D. Burrow, Diane B. Bright, Tim D. Riley, and James H. Graham, and published by the UF Department of Soil and Water Science, July 2015.